Stakeholder theory: origins, developments and contributions to the field of business and society: Théorie des parties prenantes : origines, développements et contributions au champ de l'entreprise et la société - Morad, NADI (African Scientific Journal, 2021)
After 36 years of its introduction into the field of management, stakeholder theory is ubiquitous today. We can easily see a spread of its terminology everywhere, whether in scientific journals or in the speeches of managers and company websites. Especially when it comes to the relationship between the business and its environment. However, despite this widespread popularization, little is known about its real contribution to the evolution of knowledge and practice of company management. Indeed, it is approached in the French-speaking literature in a fragmented way, according to the objectives of each researcher. And rare are the works that have brought together the existing, in particular his various contributions to the field of CSR, that he has mobilized widely. Thus, the objective of this paper is to review the origins, developments and contribution of stakeholder theory, in particular for the research field of business and society Résumé Après 36 de son introduction dans le champ de management, la théorie des parties prenantes est aujourd’hui omniprésente. On constate aisément une diffusion partout de sa terminologie, que ce soit dans les revues scientifiques ou dans les discours des dirigeants et les sites des entreprises. Surtout lorsqu’il s’agit de la relation entre l’entreprise est son environnement. Cependant, malgré cette grande vulgarisation, on sait peu sur sa réelle contribution dans l’évolution de la connaissance et la pratique du management de l’entreprise. En effet, elle est abordée dans la littérature francophone de façon fragmentée, selon les objectifs de chaque chercheur. Et rare sont les travaux qui ont regroupé l’existant, notamment ses différentes contributions pour le domaine de la RSE, qu'il l’a mobilisée largement. Ainsi, l’objectif de ce papier est de revenir sur les origines, les développements et l’apport de la théorie des parties prenantes, en particulier pour le champ de recherche de l’entreprise et la société. Mots clés : Théorie des parties prenantes, RSE, entreprise et société, Apports, limites